Exploring Factors Contributing to Satisfaction and Willingness to Recommend in Scuba Diving Tourism - MAT ALI, Siti Murni; SET, Kalsitinoor; NGAH, Abdul Hafaz (Journal of Environmental Management and Tourism, 2022)
Satisfaction has become a major concern for the tourism businesses as it contributed to the willingness to recommend. This paper explores factors that contributed to satisfaction and willingness to recommend scuba diving tourism. The purposive sampling method was used to select the respondent for the survey which used questionnaires in Redang Island, Malaysia. By using SmartPLS, the study analysis confirms the importance of services, facilities, and destination image towards satisfaction and willingness to recommend scuba divers. Perceived crowdedness was found to have moderating effects on the proposed relationship. The study also highlights the unsupported relationship between lodging and satisfaction. These findings lead to further discussion on the theoretical and managerial implications for scuba diving tourism.